An Investigation of the Restorative Benefits of Different Spaces in an Urban Riverside Greenway for College Students—A Simple Autumn Outdoor Experiment - Zhu, Chunyan; Li, Jingzhu; Luo, Jinming; Li, Xi; Li, Tianhui; Wang, Wei; Fu, Shanshan; Zeng, Weizhen (Sustainability, 2024)
Greenways are important natural environment places in cities, which have a great restorative effect on human physiological and mental health. The restoration effect of urban greenways on the physical and mental health of urban residents is affected by the type of greenway space. In order to reveal the restorative effects of different types of urban waterfront greenway spaces on the human body and explore restorative environmental factors, this paper firstly used the expert survey method to construct an AHP (analytic hierarchy process) model, which yielded three types of criterion-level indicators and eight types of sub-indicators. Second, taking Nanxun Avenue Greenway in Wenjiang District, Chengdu City, Sichuan Province, China, as an example, it was divided into three types of greenway spaces—waterfront space, underwood space, and lawn space—on the basis of field surveys. A total of 30 subjects participated in this outdoor experience and collected their physiological and psychological data. The results of the experiment showed that all three types of spaces in the Nanxun Avenue Greenway had a restorative effect on human physical and mental health, and all of them were effective in lowering blood pressure and heart rate, as well as eliminating negative emotions and increasing positive emotions for most of the participants. The waterfront space had the best restorative effect, followed by the underwood space and the lawn space. The main restorative environmental factors differed among each of the three types of spaces. This paper provides insights and examples for exploring the restorative benefits of urban greenways.